2023
DOI: 10.1002/cb.2193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mental accounting on purchase decision processes: A systematic review and research agenda

Florian Skwara

Abstract: This paper aims to systematically analyze and synthesize the existing research published on mental accounting and purchase decision processes by conducting a systematic literature review. Specifically, the paper aims to answer the question: “What are the effects of mental accounting on purchase decision processes?” Therefore, it identified 110 papers which contribute to achieving the research objective and which were selected using the same data collection, data analysis, and quality standards. After reviewing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 121 publications
0
3
0
Order By: Relevance
“…, 2021; Alsharif et al. , 2023a, b; Skwara, 2023). Our research is closely aligned with the impact of mental accounts on consumer purchasing and decision-making (Liu et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2021; Alsharif et al. , 2023a, b; Skwara, 2023). Our research is closely aligned with the impact of mental accounts on consumer purchasing and decision-making (Liu et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2017). In purchase decision-making processes, the impact of mental accounts can be categorized into four main themes: the source of funds, intended use of funds, pricing, and payments (Skwara, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chu and Liao (2010) found that consumers' awareness of future online resale potential can significantly influence their purchase decisions. Consumers typically perceive payments for desired products as losses, while product usage benefits are seen as gains (Skwara, 2023). By combining purchase and resale, consumers offset losses with gains, mitigating the sense of loss (Zhang et al, 2022).…”
Section: Drive Reduction Theorymentioning
confidence: 99%
“…Menurut Prayanthi (2022) pencatatan dapat membantu dalam mendokumentasikan pengeluaran ataupun pemasukan. Mengelola keuangan sangat penting dilakukan dengan tujuan agar uang yang keluar tidak melebihi uang yang diterima (Skwara, 2023). Dengan memperhatikan mental accounting mahasiswa juga dapat memperkirakan pengeluaran apa saja yang mereka lakukan.…”
Section: Mahasiswa Indekos Dalam Mengelola Pengeluaran Harianunclassified